Spain (International Monetary Fund, 2020)
The COVID-19 pandemic will exacerbate Spain's already large inclusion gap. Responding in the recovery with policies that support social objectives should be a key priority and calls for several structural changes. This paper summarizes some of the main drivers behind the social dispersion, which pre-dates the COVID-19 crisis, and policy options. The focus is on how to address the fragmented labor market, tackle pressures on rental-housing affordability, and lower the gender pay gap.1, 2
10.5089/9781513560984.002
Keywords: Graue Literatur; Business and Economics; Social Science; Infrastructure; Women''s Studies'; Gender Studies; Economics of Gender; Non-labor Discrimination; Wages; Compensation; and Labor Costs: General; Demand and Supply of Labor: General; Labor Economics: General; Wages; Compensation; and Labor Costs: Public Policy; Labour; income economics; Gender studies; women & girls; Social discrimination & equal treatment; Macroeconomics; Gender studies; gender groups; Labor markets; Gender inequality; Labor; Minimum wages; Gender; Wages; Women; Labor market; Sex discrimination; Labor economics